Developmental stages of Lampides boeticus (Lepidoptera : Lycaenidae) and their association with the host plant Lupinus nanus (Fabaceae) (Dhaka University Journal of Biological Sciences, 2015)
Developmental stages in the life cycle of lycaenid butterfly, Lampides boeticus (Lepidoptera : Lycaenidae) and their association with the host plant (Lupinus nanus) (Fabaceae) were examined both in the laboratory under 29 ± 3ºC temperature with RH 78 ± 2% and field conditions. The oviposition behaviour, incubation and larval‐pupal period of the butterfly and its association with L. nanus were studied. The host plant association and duration of developmental stages were given importance. Duration of life cycle (egg to adult) was 19 ‐ 21 days. Eggs, four larval instars and pupal stages were distinct. Lampides boeticus was found deeply associated with L. nanus to complete its life cycle. This association with host plant was characterized and evidenced by the use of host leaves, flowers, buds and seeds ( pods) both in the larval (11 ‐ 13 days) and pupal (4 ‐ 6 days) stages. The incubation period, different larval instars and pupal stage were found to be associated deeply with the phenological phases of the host plant.Dhaka Univ. J. Biol. Sci. 24(1): 43-52, 2015 (January)